Antifungal Activity of Silver Ions and Nanoparticles on Phytopathogenic Fungi - Jo, Young-Ki (Plant disease, 2009)
Silver in ionic or nanoparticle forms has a high antimicrobial activity and is therefore widely used for various sterilization purposes including materials of medical devices and water sanitization. There have been relatively few studies on the applicability of silver to control plant diseases. Various forms of silver ions and nanoparticles were tested in the current study to examine the antifungal activity on two plant-pathogenic fungi, Bipolaris sorokiniana and Magnaporthe grisea. In vitro petri dish assays indicated that silver ions and nanoparticles had a significant effect on the colony formation of these two pathogens. Effective concentrations of the silver compounds inhibiting colony formation by 50% (EC50) were higher for B. sorokiniana than for M. grisea. The inhibitory effect on colony formation significantly diminished after silver cations were neutralized with chloride ions. Growth chamber inoculation assays further confirmed that both ionic and nanoparticle silver significantly reduced these two fungal diseases on perennial ryegrass (Lolium perenne). Particularly, silver ions and nanoparticles effectively reduced disease severity with an application at 3 h before spore inoculation, but their efficacy significantly diminished when applied at 24 h after inoculation. The in vitro and in planta evaluations of silver indicated that both silver ions and nanoparticles influence colony formation of spores and disease progress of plant-pathogenic fungi. In planta efficacy of silver ions and nanoparticles is much greater with preventative application, which may promote the direct contact of silver with spores and germ tubes, and inhibit their viability